Recovery of Aluminum and Iron from Coal Fly Ash Waste using Microwave Assisted Extraction (MAE) for Coagulant - Wahyu Sugeng Bagus Satrio; Vini Fita Sari; Renova Panjaitan; Susilowati; Dyah Suci Perwitasari; Sri Redjeki; Nurul Widji Triana (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Coal fly ash is an industrial waste containing aluminium and iron with potential for reuse as coagulant materials. This study aimed to recover aluminium and iron from coal fly ash using Microwave Assisted Extraction (MAE) with hydrochloric acid, and to evaluate their application in textile wastewater treatment. Variations in HCL concentration (1-5 M) and extraction time (30-50 minutes) were examined to determine optimal conditions. The result showed that the highest recovery was achieved at 5 M HCL and 40 minutes, with aluminium and iron recovery of 48.4% and 78%. The extracted aluminium and iron were successfully applied as coagulants in textile wastewater treatment, resulting in significant reductions in color to 30 Pt-Co, turbidity to 26.9 NTU, and TSS to 46 mg/L, while maintaining a stable pH value at 6. All treated wastewater parameters complied with the applicable discharge standards. These finding demonstrate that MAE is an effective and promising approach for recovering aluminum and iron from coal fly ash and production sustainable coagulant for industrial wastewater treatment. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9 : Industry, Innovation, and InfrastructureSDG 12 : Responsible Consumption and ProductionSDG 13: Climate ActionSDG 15: Life on Land